Relationship between Endothelial Dysfunction and Prevalence of Chronic Kidney Disease: The Circulatory Risk in Communities Study (CIRCS) - Li, Yuting (J Atheroscler Thromb, 2021)
Aims: Patients with chronic kidney disease (CKD) have a higher burden of cardiovascular morbidity and mortality than the general population. Endothelial dysfunction has been suggested to play a role in both glomerular filtration rate loss and cardiovascular damage. Thus, the present study aimed to evaluate the relationship between endothelial dysfunction and the prevalence of CKD in the general Japanese population. Methods: We conducted a cross-sectional study of 1042 men and women aged 30–81 years in two communities under the Circulatory Risk in Communities Study between 2013 and 2017. Endothelial function was evaluated by percent change of brachial artery flow-mediated dilation (%FMD) before and after the cuff inflation. Results: Among the total 1042 participants, there were 62 cases of CKD (~6%). The multivariable odds ratios (ORs) (95% confidence intervals [CIs]) of CKD according to quartiles of %FMD were 2.02 (0.68–5.99), 3.56 (1.27–9.94), and 3.14 (1.10–8.93) for the third to lowest quartile compared with the highest %FMD quartile; p for trend=0.02. The respective multivariable ORs (95% CIs) of CKD in subjects without antihypertensive medication use (39 cases among 886 subjects) were 1.83 (0.46–7.33), 3.41 (0.92–12.61), and 4.60 (1.22–17.31); p for trend=0.01, and that for one-point decrement in %FMD was 1.16 (1.00–1.35); p for interaction with the status of antihypertensive medication use was 0.12. Conclusions: Our cross-sectional study suggested the relationship between endothelial dysfunction and the higher prevalence of CKD in the general Japanese population.